’Ūġārīt wa-Mārī (’awwalan): al-’ilāqāt fī al-’aṣr al-burūnzī al-ḥadīṯ - Yūn, Marġarīt
Marguerite Yon; Ugarit and Mari (Part One): Mutual Relations in the Late Bronze Age; ersch. 1986?; in Arabic, translated by Baš?r Zuhd?.